PERAN KOMUNIKASI KORPORAT PENGEMBANG KAWASAN INDUSTRI DI KABUPATEN BEKASI DALAM MEREDAM KONFLIK SOSIAL MASYARAKAT - Yuniarti, Tatik; Samariansyah, Iwan (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
Bekasi regency, West Java, grew into the International Economic Zone (ZONI). The rapid pace of industry put Bekasi district as one of the largest industrial area in Southeast Asia. But about 25 percent of the total indigenous population in Bekasi still live in poverty. This is in contrast occurs between the native people living in an industrial area. The difference is what often led to conflict between the two communities. In connection with the above-mentioned problems, this study aims to (1) determine how the role of corporate communications (corporate communication) conducted in the industrial park development company with local communities to keep the conflict from getting stronger. (2) To analyze the pattern or model of communication by the company to maintain the social order remains conducive. This study was conducted on two industrial zones in Bekasi, PT Jababeka, and PT Lippo Cikarang. Both companies were selected as research subjects because during active communication with the local communities that surround industrial area. The results showed that both regional development company, PT Lippo Cikarang Tbk and PT Jababeka Tbk is still trying to establish a harmonious relationship with the surrounding community through a number of CSR programs. However, the activities carried out still largely charity, or have not been sustained. Yet local communities around the industrial area of sustainable want help to improve their lives